Systematic Identification of Target Genes for Cellular Morphology Engineering in Synechococcus elongatus PCC7942 - Zhang, Mingyi; Qiao, Cuncun; Luan, Guodong; Luo, Quan; Lu, Xuefeng (Frontiers in Microbiology, 2020)
Cyanobacteria are serving as promising microbial platforms for development of photosynthetic cell factories. For enhancing the economic competitiveness of the photosynthetic biomanufacturing technology, comprehensive improvements on industrial properties of the cyanobacteria chassis cells and engineered strains are required. Cellular morphology engineering is an up-and-coming strategy for development of microbial cell factories fitting the requirements of industrial application. In this work, we performed systematic evaluation of potential genes for cyanobacterial cellular morphology engineering. Twelve candidate genes participating in cell morphogenesis of an important model cyanobacteria strain, Synechococcus elongatus PCC7942, were knocked out/down and overexpressed respectively, and the influences on cell sizes and cell shapes were imaged and calculated. Targeting the selected genes with potentials for cellular morphology engineering, the controllable cell lengthening machinery was also explored based on the application of sRNA approaches. The findings in this work not only provided many new targets for cellular morphology engineering in cyanobacteria, but also helped to further understand the cell division process and cell elongation process of Synechococcus elongatus PCC7942.